2021
DOI: 10.3389/fpls.2021.621064
|View full text |Cite
|
Sign up to set email alerts
|

Habitat Quality Differentiation and Consequences for Ecosystem Service Provision of an Amazonian Hyperdominant Tree Species

Abstract: Ecosystem services of Amazonian forests are disproportionally produced by a limited set of hyperdominant tree species. Yet the spatial variation in the delivery of ecosystem services by individual hyperdominant species across their distribution ranges and corresponding environmental gradients is poorly understood. Here, we use the concept of habitat quality to unravel the effect of environmental gradients on seed production and aboveground biomass (AGB) of the Brazil nut, one of Amazonia’s largest and most lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 113 publications
(164 reference statements)
0
4
0
Order By: Relevance
“…Thompson et al 2012 also indicate that spatial planning for biodiversity conservation objectives in tropical and sub-tropical forests needs to be more area-specific than for carbon management, given the uniqueness of some species assemblages. In addition, research findings focused on Brazil nut (Thomas et al 2018;Thomas et al 2021) revealed that both fine-scale structuring and environmental gradients across the distribution range of hyperdominant trees species -which contribute most to ecosystem services such as carbon sequestration and production of nuts -influence the quantity of ecosystem services delivered. Novel forest ecosystems were observed, but it is not clear whether they will be able to sustain the provision of ecosystem goods and services in the future (Thompson et al 2012).…”
Section: Understanding the Relationships Between Forest Biodiversity ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Thompson et al 2012 also indicate that spatial planning for biodiversity conservation objectives in tropical and sub-tropical forests needs to be more area-specific than for carbon management, given the uniqueness of some species assemblages. In addition, research findings focused on Brazil nut (Thomas et al 2018;Thomas et al 2021) revealed that both fine-scale structuring and environmental gradients across the distribution range of hyperdominant trees species -which contribute most to ecosystem services such as carbon sequestration and production of nuts -influence the quantity of ecosystem services delivered. Novel forest ecosystems were observed, but it is not clear whether they will be able to sustain the provision of ecosystem goods and services in the future (Thompson et al 2012).…”
Section: Understanding the Relationships Between Forest Biodiversity ...mentioning
confidence: 99%
“…This indicates that the local knowledge that guides Brazil nut extraction and keeps it within sustainability levels is robust, and that productivity estimates could be entrusted to harvesters, since taking actual measurements is very expensive and labour-intensive (ibid.). Two other research papers demonstrate the value of productivity data collected from local harvesters for testing complex hypotheses, including fine-scale processes that shape the provision of ecosystem services (Thomas et al 2018;Thomas et al 2021), such as the distance from individuals of the same species and density-dependence mechanisms that seem to regulate the spatial distribution of tree diversity in natural forests (Thomas et al 2018).…”
Section: Citizen Science and Local Knowledge Supporting Conservationmentioning
confidence: 99%
“…Habitat quality is generally defined as the potential of ecosystems to provide suitable conditions for biological conservation, which has fundamental importance to biodiversity maintenance and ecosystem service functions [1][2][3]. Over the decades, land use changes have dramatically affected habitat quality [4].…”
Section: Introductionmentioning
confidence: 99%
“…In water-scarce temperate drylands, more attention has been paid to the dynamic interactions between rainfall and vegetation coverage and the ESs they provide (Wang et al, 2011;Rohatyn et al, 2018;Wang H. et al, 2022). In areas with abundant hydrothermal conditions, studies have revealed the effects of forest supply and support services on precipitation gradients (Alamgir et al, 2016;Thomas et al, 2021). In addition, the influence of temporal variation in precipitation on forest ESs is also one of the hotspots, e.g., the effects of inter-annual and intra-annual temporal dynamics of precipitation on forest area and regulation services (soil erosion, nutrient retention and etc.)…”
Section: Introductionmentioning
confidence: 99%